Marine Surface Films Chemical Characteristics, Influence on Air-Sea Interactions and Remote Sensing - Gade, Martin; Hühnerfuss, Heinrich; Korenowski, Gerald M. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Since the late 1960s, various groups have investigated the influence of marine surface films on mechanisms dominating energy and mass transfer across the ocean/atmosphere interface. However, a compendium summarizing the state-of-the-art research in this field is still missing. The book fills this gap and transfers the accumulated knowledge to the scientific community. After a brief historical chapter basic chemical insights are presented, followed by theoretical and experimental approaches carried out in laboratory facilities. Air-sea interaction experiments are then described and finally, remote sensing applications with sea slicks and crude oil spills are presented.